Development of integrated anaerobic-aerobic bioreactors for the complete degradation of synthetic wastewater containing mono and diazo dye - Murali Viswanathan (School of Environmental Engineering, Universiti Malaysia Perlis, 2014)
The present study aimed to develop the bioreactor which able to perform in effective color and intermediates removal of azo dye. The study conducted one anaerobic and three different integrated anaerobic-aerobic bioreactors namely, Upflow Anaerobic Sludge Blanket (UASB) reactor, Integrated Anaerobic-Aerobic Coconut Fiber (IAACF) reactor, Integrated Anaerobic-Aerobic Gravel and Coconut Fiber (IAAGCF) reactor and Integrated Anaerobic-Aerobic Granular Activated Carbon (IAAGAC) reactor. Performance of the above all reactors against the degradation of synthetic wastewater containing mono azo dye Methyl Orange (MO) and diazo dye Reactive Red 120 (RR120) were assessed in different influent color concentrations.